Cost-Effectiveness Analysis of Early Reconstruction versus Rehabilitation and Delayed Reconstruction for ACL Tears - Mather, Richard C. (Am J Sports Med, 2014)
BACKGROUND: An initial anterior cruciate ligament (ACL) tear can be treated with surgical reconstruction or focused rehabilitation. The KANON (Knee Anterior cruciate ligament, NON-surgical versus surgical treatment) randomized control trial compared rehabilitation plus early ACL reconstruction (ACLR) to rehabilitation plus optional delayed ACLR and found no difference at two years by intention to treat analysis of total KOOS scores. The purpose of this study was to compare the cost-effectiveness of early versus delayed ACLR. METHODS: A Markov decision model was constructed for a cost-utility analysis of early reconstruction (ER) versus rehabilitation plus optional delayed reconstruction (DR). Outcome probabilities and effectiveness were derived from two sources: the KANON Study and the Multicenter Orthopaedic Outcomes Network (MOON) database. Collectively, these two sources provided data from 928 ACL patients. Utilities were measured by the SF-6D. Costs were estimated from the societal perspective in 2012 U.S. dollars. Costs and utilities were discounted in accordance with the United States Panel on Cost-Effectiveness in Health and Medicine. Effectiveness was expressed in quality-adjusted life years gained (QALYs). Principal outcome measures were average incremental costs, incremental effectiveness (as measured by QALYs), and net health benefits. Willingness-to-pay was set at $50,000, the currently accepted standard in the U.S. RESULTS: In the base case, the ER group resulted in an incremental gain of 0.28 QALYs over the DR group with a corresponding lower overall cost to society of $1572. Effectiveness gains were driven by the low utility of an unstable knee and the lower utility for the DR group. The cost of rehabilitation and the rate of additional surgery drove the increased cost of the DR group. The most sensitive variable was the rate of knee instability after initial rehabilitation. When the rate of instability falls to 51.5%, rehabilitation plus optional delayed ACLR is less costly and when it falls below 18% it becomes the preferred cost-effective strategy. CONCLUSIONS: An economic analysis of the timing of ACLR using data exclusively from the KANON trial, MOON cohort, and national average reimbursement revealed that early ACLR was more effective (improved QALYs) at a lower cost than rehabilitation plus optional delayed ACLR. Therefore, early ACLR should be the preferred treatment strategy from a societal health system perspective.